MEMORY Bondarenko VICTOR MIKHAILOVICH (1940-2014) - IMINAMN, GU group "of the Institute of Microbiolo (Annals of Mechnikov’s Institute, 2020)
His memory will forever remain in the hearts who knew his staff, medical personnel, relatives and friends.